Neuroprotection and anxiety like behavior reduction of Allium hirtifolium and Astragalus hamosus in the Aβ-injected rat - Z. Bahaeddin; A. Yans; F. Khodagholi; S. Sahranavard (Iranian Society of Pharmacognosy, 2016)
Background and objectives:Traditional medicine is an important approach to achieve new therapeutic strategies in basic and clinical pharmacology. Allium hirtifolium Boiss. and Astragalus hamosus L. have been mentioned in Iranian Traditional Medicine references for a kind of dementia with features and symptoms similar to those of Alzheimer's disease (AD). In the present study, the neuroprotective effect of these herbs has been evaluated as new therapies in neurotoxicity model. Methods: Two separate groups of rats were fed with A. hirtifolium or A. hamosus extract (100 mg/kg/day) from 1 week before amyloid beta (Aβ) injection, for 16 consecutive days. One day after the last oral administration, behavioral test was done. The effect of these two extracts were assessed in anxiety-like behavior test using elevated plus maze. Furthermore, molecular pathways involved in apoptosis were assessed by Western blotting analysis. Results: The results showed that oral administration of both A. hirtifolium and A. hamosus decreased anxiety-like behavior and ameliorated the effect on apoptosis factors including Bax, Bcl-2 and caspase-3 in the rats with intra-hippocampal injection of Aβ. Conclusion: The results of this study revealed the potential neuroprotective properties of A. hirtifolium and A. hamosus as herbal remedies that could play a role in fostering healthy aging and be considered as useful candidates in decreasing AD related symptoms.